Analisis pengaruh intensitas transaksi digital, gaya hidup digital, dan kepercayaan terhadap literasi keuangan pengguna E-wallet - Okta Angriani; Ika Rosyada Fitriati (Universitas Negeri Surabaya, 2026)
This study aims to analyze the influence of Digital Transaction Intensity, Digital Lifestyle, and Trust on Financial Literacy of e-wallet users. The research approach used is explanatory research with quantitative methods. Data were collected through questionnaires distributed to 100 Generation Z e-wallet users in Semarang City. The collected data were analyzed using multiple regression using SPSS software. The results of the analysis indicate that digital transaction intensity has no significant effect on financial literacy. Meanwhile, digital lifestyle and trust have a significant effect on financial literacy. Simultaneously, Digital Transaction Intensity, Digital Lifestyle, and Trust have a significant effect on Financial Literacy. The coefficient of determination value shows that the three independent variables are able to explain the dependent variable by 59.2%, while the remainder is influenced by other variables outside this study.